Artificial lithography in emergent categories of user digital communication - Argota-Pérez, Yadira (2025)
The objective of the study was to construct an artificial lithography within emergent categories of user digital communication. Between May and September 2024, a systematic literature review in English was conducted on Google Scholar (2020-2024) utilizing the Prisma methodology. The search addressed digital communicative practices, the impact of social networks, and user interaction. Using artificial lithography, connections between categories were established based on link quadrants and prior citations. It was found that studies on digital communication and interaction in social networks fell into three categories: digital communicative practices (42%), impact of social networks (30%), and user interaction (28%). Notable production peaks occurred in 2020 and 2023, reflecting a growing interest since 2017 and the influence of the pandemic. It is discussed that the literature evidences the adaptation of digital communicative practices and the increasing role of social networks in key sectors, highlighting the importance of user interaction in brand perception. This necessitates diverse approaches to understand the complex dynamics of digital communication. It is concluded that the categories of digital user communication demonstrated autonomous and creative content for transforming a digital ecosystem, promoting active and collaborative interactions, redefining structures, and generating dynamic and participatory communication.